Development of Career Cards Counseling Guidance Media to Improve Student's Career Planning - Akhmad Harum Harum; Nur Wahyuni; Abdullah Sinring; Muhammad Anas (ILIN Institute Makassar, 2023)
This research aims to develop career card media based on career information services and produce valid, practical, effective, and responsive media. The existence of the media is expected to help the career guidance process at school. The method used is the research and development method of the Borg and Gall model with steps: 1) potential problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, and 7) final product. The subjects in this study were seventh-grade students of SMP Negeri 51 Makassar. The data collection instrument used is a questionnaire given to material experts, media experts, practitioners, and respondents (students) to see the feasibility of the developed media. The data analysis technique used is qualitative data analysis and quantitative descriptive analysis. The results of this study indicate that 1) an overview of the needs of career card game media to improve students' understanding of career planning. 2) description of the prototype of career cards game media in increasing students' understanding of career planning. 3) description of the validity and practicality of career cards media in increasing the understanding of student career planning career cards media developed by researchers have been valid and practical to use in providing counseling guidance services specifically on career guidance at the junior high school level at SMP Negeri 51 Makassar